A Ribonuclease Isolated from Wild Ganoderma Lucidum Suppressed Autophagy and Triggered Apoptosis in Colorectal Cancer Cells - Xiuli Dan; Wenlong Liu; Jack WONG; Tzi Bun Ng (Frontiers Media S.A., 2016)
The mushroom Ganoderma lucidum (G. lucidum) has been consumed in China as a medicine for promoting health and longevity for thousands of years. Due to its paramount and multiple pharmaceutical effects, G. lucidum has received considerable attention from researchers and its chemical constituents as well as their respective functions were gradually unveiled by using modern research methods. Herein, we reported the isolation of a protein (GLR) with anti-colorectal cancer activities from G. lucidum. This protein is a 17.4-kDa RNA degrading enzyme (ribonuclease) and was purified by using liquid chromatography procedures. GLR manifested potent anti-proliferative and anti-colony formation activities on HT29 and HCT116 colorectal cancer cells by inducing cell cycle arrest in G1 phase through the regulation of cyclin D1 and P53 expression. GLR was demonstrated to induce cell apoptosis in HCT116 cells by activating unfolded protein response and caspase-9 regulated pathways. Besides, the ability to undergo autophagy which is a stress adaption mechanism to cope with metabolic crisis was significantly suppressed by GLR treatment in HCT116 cells. The activation of apoptosis in GLR-treated HT29 cells was, however, independent of caspase-9 and the suppression of autophagy was also relatively minor. Thus the apoptosis of HT29 cells triggered by GLR was much milder than that in HCT116 cells. Our findings show that the RNase from G. lucidum may be one of the bioactive components that contribute to the anti-colorectal cancer activity of G. lucidum.